Multipurpose cadastre for campus room appraisal - Satrio Muhammad Alif; Agung Pandi Nugroho; Bambang Edhi Leksono (Journal of Science and Applicative Technology, 2019)
The use of fundamental components of multipurpose cadastre which can be used as basic information and backbone for government policy with geographical information system as a tool are applied in this research method to appraisecampus room. The process to appraise of the facilities in a room begins with collecting facilities data which related to attribute data and defining room boundary which related to spatial data. Room appraisal are analysed by firstly calculate room valuebasedon facilities and activity hours.The method to calculate room value is comparison of quantity and functionality of facilities in every room. Thorough analysis is conducted to separate room value data containing human errors. The determination of which category (high, medium, low) every room fit in is based on distribution of value of every room value which is free of human errors. Room appraisal using this research method will lead to optimize every campus room especially low category room. This approach is also effective way to record number of rooms and facilities of campus comprehensively. Keywords: Multipurpose cadastre, Appraisal, Geographic Information System